Kajian Eksperimental Perilaku Dinding Bata Terkekang Berplester akibat Beban Siklik - Dyah Kusumastuti; Indriana Apriani; Made Suarjana (Department of Civil Engineering, Diponegoro University, 2025)
Confined masonry walls are commonly found in non-engineered housings in Indonesia. To better understand their behavior and to find improvement to the current practice, experimental studies have been conducted using full-scale (3m × 3m) wall specimens, which represent simple housing wall panels. In this research, the performance of plastered confined masonry walls in resisting lateral loads was studied experimentally. Three wall specimens were constructed following general construction practice in Indonesia. All specimens were plastered on both sides. Model 1 was constructed without continuous anchorage, Model 2 with two continuous anchorages with 1m spacing, and Model 3 with two continuous anchorages with 0.5m spacing. The specimens were subjected to cyclic in-plane lateral loads. The parameters evaluated were damage pattern and failure mechanism, load capacity, stiffness, ductility, and energy dissipation. The study revealed that adding plaster improved the wall’s lateral capacity. The continuous anchorage shows less significant improvement on plastered walls compared to non-plastered walls, but still increased stiffness, ductility, and energy dissipation. The study verifies that having plaster and continuous anchorage improve structural performance while delaying damage. Analytical study reveals that all models have adequate capacity to resist the design seismic load based on the current code.